Islamic Education Teachers and the Process Approach: Challenges in Islamic Education Instruction at Inclusive School of SD Muhammadiyah 12 Pamulang - Ummah Karimah; Rusjdy S. Arifin; Siti Shofiyah; Azie Fahrazie Yabes; Nisdiar Dwi Nugraha (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Recently, the interest of parents who have children with special needs with various diagnoses has increased to send their children to SD Muhammadiyah 12 Pamulang. It is the school's duty to approach students to get special treatment in facilitating the learning process at school. However, PAI teachers do not have special expertise in inclusive education. This study is to discuss the challenges faced by PAI teachers who teach in inclusive schools. The data collection technique used in this study was through interviews with school principals, vice principals for curriculum, and all Islamic education teachers. The data obtained were analyzed through the stages of data reduction, presentation of patterned data, and drawing conclusions. The results showed that the challenges faced by PAI teachers were difficulties in communicating and controlling the behavior of children with special needs even though children with special needs have a good level of academic intelligence, including memorizing the Qur'an. Another challenge found is experiencing a bad mood while studying, teachers are required to have full patience because sometimes children with special needs are indifferent and stare blankly. After conditioning children with special needs to have a good mood, the PAI teacher slowly returns to delivering lessons.